Magnetic Anisotropy and the Paleosecular Variation Record in Stalagmites from Njirak Cave, East Java: The Effect of Detrital Magnetite Emplaced in Small Cavities by Flooding Events - Satria Bijaksana; Siti Zulaikah; Joseph Paul Hodych (Indonesian Journal of Physics, 2009)
Magnetic anisotropy and remanence were measured for 33 samples from the axis of two stalagmites from Njirak Cave in East Java. All 33 samples were stepwise demagnetized with alternating fields, but only 16 were stable enough to yield reliable characteristic remanence directions. These directions differ, especially in declination, from the present Earth’s field direction and agree for samples of about the same age from both stalagmites, suggesting that the Earth’s field at Njirak Cave maintained a declination averaging 23° and an inclination averaging −23° for most of the past 2,500 years. Anisotropy of magnetic susceptibility is high, averaging 5.8%. The minimum susceptibility axes are nearly horizontal with scattered declinations; whereas the maximum susceptibility axes tend to be steeply inclined (average inclination is 51°). This implies that the long axes of the mainly multi-domain magnetite grains tend to be steeply inclined (rather than horizontal, as expected if the magnetite were in horizontal detrital layers). We suggest that this is due to the magnetite being in flood-emplaced detritus adhering to the steeply-inclined sides of small (2 to 5 mm) cavities that cut across and are sealed off by the stalagmites’ horizontal calcite growth layers. Steeply inclined maximum susceptibility axes should help detect such stalagmites, whose quality of paleosecular variation record may be lowered by magnetite-bearing cavities.